Can Less Ever Be More? A Model of Emotion Regulation Repertoire of Social Support (ERROSS). (April 2021) - Stelzer, Eva-Maria; O'Connor, Mary-Frances
Do people really fare better if they can rely on many social ties? Research suggests that benefits of interpersonal emotion regulation (ER) can be derived from both large and small social networks. Building on the intrapersonal regulatory flexibility model, we propose the emotion regulation repertoire of social support (ERROSS) model that views effective socioemotional support as the combination of network size and ER strategies, resulting in a repertoire of ER resources one can draw on. Best outcomes in mental health should follow from both a large network and a diverse repertoire of strategies. ERROSS is applied as an example in the context of bereavement, and specific contributions of the model are highlighted.